On the Spin Behaviour of Iron(II)-Dipyridyltriazine Complexes and Their Performance as Thermal and Photonic Spin Switches - Hain, Sophie K.; Heinemann, Frank Wilhelm; Gieb, Klaus; Müller, Paul; Hoerner, Gerald; Grohmann, Andreas (European Journal of Inorganic Chemistry, 2010)
The temperature-dependent and photodynamic spin behaviour of three iron(II) complexes with different 2,6-dipyridyl-4-phenyltriazine ligands L1-L3 was investigated in the solid state and in solution (DMSO). The ligands differ in the substituent R in the 4-position of the phenyl ring (L1: R = H; L2: R = OCH(3); L3: R = SAc), which allows the electronic properties of the ligands to be finetuned. The magnetic data for the complex [Fe(L3)(2)](BF(4))(2) in the solid state indicate an incomplete spin transition to the high-spin form upon warming from liquid helium temperature, reaching about 30% at 400 K, There is circumstantial evidence for paramagnetic contributions compatible with spin transitions, namely, temperature -dependent NMR spectroscopic line shifts and line broadening in solution (DMSO). However, an efficient thermally induced spin crossover in solution is hindered by the substitution lability of the complexes, as has been detected and analyzed in an extended temperature-dependent UV/Vis spectroscopic study. Essentially unaffected by thermally induced Substitution lability, the transient dynamics of the iron(II) complexes after nanosecond laser flash excitation of their metal-to-ligand charge-transfer bands provide good evidence for efficient photoinduced spin transitions in solution in all cases. The range of measured lifetimes of the high-spin quintet states is in accord with previously published data. Importantly, in our series of iron(II) complexes, the lifetimes of the high-spin state reflect the electron-donating character of the ligands.
Keywords: Iron; Spin crossover; Thermodynamic stability; N ligands; Magnetic properties